Anaerobic Digestion of Sewage Sludge Mixture for the Reduction of Indicator and Pathogenic Microorganisms - Poudel, Ram Chandra; Joshi, Dev Raj; Dhakal, Nawa Raj; Karki, Amrit Bahadur (Scientific World, 2010)
Anaerobic digestion is a technique used for the sanitizing the sewage sludge before its final disposal. We determined the fate of indicators and pathogens in sewage sludge mixture subjected to mesophilic anaerobic digestion (MAD) and ambient anaerobic digestion (AAD) for 30 and 35 days respectively by culture based microbiological methods (bacteria) and formal-ether sedimentation technique (parasites). While monitoring the organisms at five days intervals, MAD effectively reduced most of the bacteria and parasites to undetectable levels than AAD. Interestingly, the highest reductions in load were observed for faecal coliforms (5.16 log10 cfu/ml) in the sewage sludge mixture of MAD which met the class A biosolid standard (USEPA). Like wise, the bacterial load reductions were negatively correlated and statistically significant (p< 0.005) with days of both digestions and the relation between total coliforms load and days of MAD experienced higher correlation coefficient (r= -0.992) and R2 (0.984) values which shows higher validity in regression model. Therefore, MAD can be considered as a promising method for reduction of indicator and pathogenic microorganisms in sewage sludge mixture. Keywords: Anaerobic digestion; Correlation coefficient; Regression model; Sewage sludge. DOI: 10.3126/sw.v8i8.3848 Scientific World Vol.8(8) 2010 pp.47-50